EFFECT OF AGE AND BREED ON ANTISPERM ANTIBODIES (ASA) IN BLOOD SERUM AND SEMINAL PLASMA OF BULLS: IMMUNOREACTIVITY OF SPERM SURFACE PROTEINS WITH ASA - ZODINSANGA, v; s, RANJNA; CHEEMA,; MAVI, P S (The Indian Journal of Animal Reproduction, 2023)
Occurrence of ASA in blood serum / seminal plasma of bulls with respect to age / breed andimmunoreactivity of sperm surface proteins with serum of bulls were determined during the present study.There was an increase of 15.3% IPA, 12.4% lgG and 9.5% lgA in serum of tested bulls with increase in age.Higher significant level of lgG antibodies and ELISA titre was detected in the serum of bulls in the age groupof> 6 years, whereas, significant level of IPA/ lgA (> 10%) and higher ELISA titre in seminal plasma wasdetected in higher percentage of bulls in the age group of 3-6 years. Occurrence of ASA (IPA/ lgG / lgA) inserum was higher in cross-bred bulls as compared to pure-bred bulls and reverse was the case in seminalplasma. Serum of all bulls showed a reaction with sperm extracted proteins on immunoblots and a total of 19antigens ( 16 ., 130 kDa) were detected, but only 4-10 antigens were recognized by serum in Sperm Extracts(SE) of respective bulls. lmmunofluorescence of sperm smears with serum of bulls predominantly stainedpost-acrosomal region, thus indicated the presence of ASA mainly against surface proteins of this region. Asimilarity in molecular weights of sperm proteins involved in various aspects of fertilization and that detectedfor immunoseropositivity with serum of presently tested bulls was found, therefore, it can be predicted thatsuch ASA may affect the fertility of bulls. In future, the functional effects of these antibodies on bull«s fertilitycan be explored.
Keywords: ASA; Cattle bulls; Age; Breed; lmmunorectivity; Sperm surface proteins